Understanding the asymmetries in ICT adoption across countries: the international digital divide - Jesus, Frederico Miguel de Campos Cruz Ribeiro de (2019)
A thesis submitted in partial fulfillment of the requirements for the degree of Doctor in Information Management, specialization in Information Technologies